Shakespearean Entrances - Ichikawa, M. author. aut Link
XI, 198 p.
Keywords: Shakespearean Entrances offer a systematic study of entrances and exits on the Shakespearean stage. Elizabethan playwrights and players not only routinely handled these movements but they also used them to bring about various effects. Through analyzing the surviving play-texts, the author attempts to identify the unspoken but standard rules that lay behind the minimal and conventionalized stage directions 'Enter' and 'Exit'/'Exeunt'. The findings provide means by which to recover effects and meanings that the original audience would have appreciated.